2022
DOI: 10.7759/cureus.25686
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Applications of the Kambin’s Triangle in Lumbar Spine Surgery

Abstract: Kambin's triangle has become the anatomical location of choice when accessing the lumbar spine to treat degenerative spinal disorders. Currently, lumbar interbody fusion is the most common procedure utilizing this space; however, with the advent of the Kambin's prism definition, advanced imaging modalities, and robotic-assisted techniques, lumbar spine surgery has become increasingly precise and less invasive. These technological and procedural advances have drastically reduced the rate of complications, impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…8,55 The inferior triangle approach, first described in 2011, 56 is safer than the traditional superior triangle approach and equally efficacious. 34,51,[56][57][58][59] Anatomically, it is a triangle superior to the dorsolateral disk that is bordered by the superior endplate of the inferior vertebral body (base of the triangle), the superior articulating facet (height of the triangle), and the imagined exiting superior nerve root (hypotenuse of the triangle) (Figure). The method for performing a TFESI via the inferior triangle is with an oblique fluoroscopic view and a needle entry point slightly lateral to the superior articular process of the vertebra caudal to the target level.…”
Section: Con: the Inferior (Kambin's) Triangle Is The Preferred Site ...mentioning
confidence: 99%
“…8,55 The inferior triangle approach, first described in 2011, 56 is safer than the traditional superior triangle approach and equally efficacious. 34,51,[56][57][58][59] Anatomically, it is a triangle superior to the dorsolateral disk that is bordered by the superior endplate of the inferior vertebral body (base of the triangle), the superior articulating facet (height of the triangle), and the imagined exiting superior nerve root (hypotenuse of the triangle) (Figure). The method for performing a TFESI via the inferior triangle is with an oblique fluoroscopic view and a needle entry point slightly lateral to the superior articular process of the vertebra caudal to the target level.…”
Section: Con: the Inferior (Kambin's) Triangle Is The Preferred Site ...mentioning
confidence: 99%
“…The presence of conjoined or scarred nerve roots, facet hypertrophy, impeding artery of Adamkiewicz, and degenerative changes to the anatomy can all affect a patient's unique spinal landscape. 47 Haijiao et al found a 17% incidence of nerve root anomalies in 376 lumbar MRI scans, whereas prior studies relied mainly on CT scans and caught only 2% of conjoined roots. 48,49 Simon et al reported that key arteries were found in both the safe zone and Kambin's triangle at statistically significant rates.…”
Section: Variability Of Kambin's Trianglementioning
confidence: 99%
“…The Kambin triangle has been considered an "anatomical corridor" and common entry point for lumbar interbody fusion, accessing Kambin's triangle in a less invasive manner indicate that the surgical procedure is more minimally invasive. 73 Dalton et al 74 designed a single-center clinical study involving 10 patients to explore the clinical application of RA access into Kambin triangle during lumbar interbody fusion, they found that the Kambin triangle were successfully accessed, interbody cage was placed successfully and safely with minimal invasiveness.…”
Section: Ra-targeted Puncture and Placement Of Endoscope Via The Inte...mentioning
confidence: 99%
“…Yang et al [ 72 ] performed 2-dimensional (2D) fluoroscopy-guided RA PTED and C-arm fluoroscopy-guided PTED in 102 patients, respectively, and found that 2D fluoroscopy-guided RA PTED had several advantages compared with C-arm fluoroscopy-guided PTED, including fewer puncture times (1.20 ± 0.42 vs. 4.84 ± 1.94), fewer fluoroscopy times (10.49 ± 2.16 vs. 17.41 ± 3.23), and shorter operation time (60.69 ± 5.63 minutes vs. 71.19 ± 5.11 minutes), suggesting that RA PTED allows the operator to plan the puncture path accurately and precisely, makes the targeted puncture easier to perform, reduces the number of punctures and fluoroscopies, shortens the operation time, optimizes the operation process, and reduces complications. The Kambin triangle has been considered an “anatomical corridor” and common entry point for lumbar interbody fusion, accessing Kambin’s triangle in a less invasive manner indicate that the surgical procedure is more minimally invasive [ 73 ]. Dalton et al [ 74 ] designed a single-center clinical study involving 10 patients to explore the clinical application of RA access into Kambin triangle during lumbar interbody fusion, they found that the Kambin triangle were successfully accessed, interbody cage was placed successfully and safely with minimal invasiveness.…”
Section: Clinical Application Scenarios For Spine Surgical Robotsmentioning
confidence: 99%